Strategi yang Digunakan Guru Bahasa Inggris dalam Mengajarkan Pemahaman Mendengarkan di Pesantren IMMIM - Tajuddin tajuddin (Universitas Al Asyariah Mandar, 2023)
The study attempts to investigate the strategies used by teachers in teaching listening comprehension and to find out the students’ responses toward the strategies used. The study took place at IMMIM Islamic Boarding School, where four teachers and 88 of first and second grade students from 4 different classes participated. The study employed descriptive method, where the data obtained through observation, questionnaires, and teachers’ interviews. The study found that the teachers used some strategies in teaching listening comprehension, which had been categorized into Bottom-up, Top-down and Metacognitive. In bottom up, it was found that teacher 1 used audio program and dictation. Teacher 2 and 3 also used the same strategies with the teacher 1, while teacher 3 also used the same strategies as teacher 1 with the addition of pronunciation, grammar and mind mapping. In top down, teacher 1 used lecturing strategies, live listening, question-answer, discussion and checking. Meanwhile, teacher 4 used lecturing strategies, question-answer, visualization and discussion. In metacognitive category, all the teacher used planning and evaluate. Students’ responses toward the strategies used were positive. It is proved by the half of the students 56 (63.6%) gave the positive respond toward the strategy